Management of Antithrombotic Therapy in Post PCI Patient Undergoing Pericardiotomy due to Large Pericardial Effusion : A case report - Dedy Irawan; Sasmojo Widito; Mohammad Saifur Rohman; Cholid Tri Tjahjono (Heart Science Journal, 2021)
Background : Stent thrombosis is a serious complication following percutaneous coronary intervention (PCI), and dual antiplatelet therapy (DAPT) is necessary to avoid it. Surgery, on the other hand, is a common cause for stopping DAPT. Because patients were exposed to the possibility of a major adverse cardiovascular event (MACE) when DAPT was stopped, this circumstance poses a clinical dilemma.Objective : This case report aimed to describe the management of antithrombotic therapy in post PCI patient requiring DAPT who underwent pericardiostomy.Case : A 69-year-old woman with large pericardial effusion without cardiac tamponade, breast cancer on chemo- therapy, heart failure stage C NYHA functional class II, chronic coronary syndrome post-DES implantation at proximal-mid LAD, and hypertension. The patient underwent pericardiotomy procedures five days after DAPT discontinuation. For the bridging therapy, continuous UFH administration was initiated at a dose of 18 IU/kg/hour after the cessation of DAPT. The UFH dose was adjusted to achieve activated partial thromboplastin time (APTT) 1.5 to 2.0 times the control value. The UFH was discontinued 6 hours before surgery. After surgery, UFH infusion was restarted 6 hours after the confirmation of hemostasis. The administration of UFH then continued until three days after DAPT was restarted. No complications were found during and after the pericar- diostomy.Conclusion : We reported an antithrombotic treatment strategy in a post PCI patient undergoing pericardiostomy with discontinuation of DAPT, which was successfully treated with UFH without any complication. The UFH has been widely used in perioperative settings as a bridging therapy during the interruption of DAPT and may be considered in this condition.